Serum immunoglobulin levels in male schizophrenic patients before and after olanzapine therapy - Mahmoud Khudhayer Oglah Hussein (المجلة العراقية للصيدلة, 2011)
Objective: To evaluate the effect of olanzapine therapy on serum immunoglobulin levels (IgA, IgG, IgM) in male schizophrenic patients after 2 months of treatment by olanzapine at a daily dose of 20 mg. Patients and Methods: Twenty-eight patients with schizophrenia were included in this study, assessment of each case was done by a psychiatric, also included a 30 healthy subjects as a control group. Serum immunoglobulin concentrations were determined for both patients and controls by Mancini Radial Immuno-diffusion method using immunoglobulin kits. For the patients group and after 2 months therapy with olanzapine at a fixed daily dose of 20 mg, serum immunoglobulins were determined again using the same method for the assay. Results: No significant difference was found between serum levels of immunoglobulin (IgA, IgG, IgM) in schizophrenic patients before therapy in comparison to controls. Also insignificant difference was found between serum immunoglobulin levels (IgA, IgG, IgM) in schizophrenic patients after 2 months of olanzapine therapy and the controls. By comparing serum immunoglobulin levels in patients with schizophrenia before and 2 months after starting olanzapine therapy, no statistically significant difference was found. Conclusion: Olanzapine as atypical antipsychotic may not have an influence on the humoral immune response as reflected by the immunoglobulin levels (IgA, IgG, IgM)